MNC response to superstitious practice in Myanmar IJVs: Understanding contested legitimacy, formal–informal legitimacy thresholds, and institutional disguise - Andrews, Tim G.; Nimanandh, Khongphu; Htun, Khin Thi; Santidhirakul, Orapin (Journal of International Business Studies, 2022)
Superstition is a pervasive informal institution affecting the decision-making of organizational actors yet remains under-studied and ill-understood in international business research. We address this lacuna through examining how Western MNCs affect – and are affected by – the use of superstition among local subsidiary managers in an emerging Asian economy. Based on interviews, archival documents, and observation, our inductive investigation reveals a complex, changing, and surreptitious relationship between MNC practice and an informal institution which, while widely practiced, remains forbidden according to its formal institutional counterpart (Buddhism) and illegal according to Myanmar state law. Initial findings showed how MNCs endorsed, acquiesced, or rejected superstitious practice based on a configuration of construed reputational risk, corporate values adherence, degree of formal institution approval, and perceived local performance impact. Subsequent MNC engagement then shifted from accommodation to resistance to manipulation in response to local managers’ disguising their ‘superstitious’ practices as Buddhism, ‘blurring’ the formal–informal institution divide in the process to secure MNC public approval. Together, our findings serve to refine and deepen existing theory into how the MNC subunit can manage its legitimacy through balancing the incompatible demands of formal and informal constituents within a contested institutional dyad.